DETEKSI EMOSI SISWA SMKS METHODIST 8 BERBASIS AI UNTUK MEMBANTU DALAM PEMBELAJARAN - Panggabean, Erwin; Apriani, Wira; Simanjorang, R. Mahdalena; Sitohang, Amran; Hasugian, Penda Sudarto; Harefa, Jikarni; Arikhifo, Arikhifo (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2025)
The research conducted through community service aims to develop artificial intelligence (AI)-based software capable of detecting students' emotions at SMKS Methodist 8 in real time, as an effort to support teachers in implementing a more adaptive and responsive learning approach. This system is designed by integrating facial recognition and emotional expression analysis through a camera, which is then processed using the Certainty Factor method to determine the confidence level of the detected emotional classification. This approach allows the system to generate emotional diagnoses with a reliable degree of confidence, based on predefined parameters. Test results have shown that the software is capable of detecting several basic emotions such as happiness, sadness, anger, and neutrality with an adequate level of accuracy. The implementation of this system in classrooms is expected to assist teachers in quickly identifying students’ emotional states, allowing learning strategies to be adjusted accordingly to improve the effectiveness of the learning process. Therefore, this technology offers an innovative solution in supporting the improvement of education quality through an approach that focuses on individual students.